Prospects to Solve the Problem of Statutory Regulation over Environment Protection in an International Aspect - SMOILOV, Samat Zh.; SERGEEV, Sergey A. (Journal of Advanced Research in Law and Economics, 2016)
The paper’s aim is a systematic research of theoretical issues in environment protection and environmental management in a review of a concept and mechanisms of international statutory regulation of these processes. The paper presents a review of a structure and a mechanism of statutory regulation over environmental relationship; the author examines and summarizes problems in establishing the statutory regulation framework for environment protection. In the paper, they identify a role and a place for economical management standards in a system of environmental law. An outcome from the research included elaborated recommendations to improve the mechanism of environment protection for a number of aspects in a positive encouragement to actors in environmental management.